Comparison of forest cover mapping results of two successive forest resource assessments of Nepal - Khanal, S.; Poudel, B. S.; Mathema, P.; Pokharel, Y. P.; Kharal, D. K. (Banko Janakari, 2016)
Not available. Banko Janakari A Journal of Forestry Information for Nepal Vol. 26, No. 1, Page:97-100, 2016